Influence of ZnO thin film crystallinity on in vitro biocompatibility. Issue 5 (22nd May 2018) - Lewinski, Nastassja A.; Avrutin, Vitaliy; Izadi, Tanin; Secondo, Lynn E.; Ullah, Md. Barkat; Özgür, Ümit; Morkoç, Hadis; Topsakal, Erdem
Graphical Abstract: Abstract: This study evaluated the cytocompatibility of single- and poly-crystalline ZnO thin films using extract and direct contact methods. Exposure to poly-crystalline ZnO extract resulted in reduced cell viability, on average 82%/70% as measured by MTS/LDH assays, respectively. Direct exposure to both single- and poly-crystalline ZnO thin films resulted in reduced cell viability, which was attributed to anoikis due to inhibition of cell adhesion to the substrate by zinc. Intracellular zinc imaging suggests that single crystalline ZnO thin films do not result in a significant change in intracellular zinc concentrations. Overall, the results suggest that single-crystalline ZnO thin films have better short-term (24 h) cytocompatibility and support their potential to serve as a biocompatible sensor material.